Cardiovascular manifestations identified by multi-modality imaging in patients with long COVID - Nobuhiro Murata; Akimasa Yamada; Hidesato Fujito; Naoki Hashimoto; Tetsuro Nagao; Yudai Tanaka; Katsunori Fukumoto; Riku Arai; Yuji Wakamatsu; Yasunari Ebuchi; Masaki Monden; Keisuke Kojima; et al. (Frontiers in Cardiovascular Medicine, 2022)
BackgroundThe possibility of permanent cardiovascular damage causing cardiovascular long COVID has been suggested; however, data are insufficient. This study investigated the prevalence of cardiovascular disorders, particularly in patients with cardiovascular long COVID using multi-modality imaging.MethodsA total of 584 patients admitted to the hospital due to COVID-19 between January 2020 and September 2021 were initially considered. Upon outpatient follow-up, 52 (9%) were suspected to have cardiovascular long COVID, had complaints of chest pain, dyspnea, or palpitations, and were finally enrolled in this study. This study is registered with the Japanese University Hospital Medical Information Network (UMIN 000047978).ResultsOf 52 patients with long COVID who were followed up in the outpatient clinic for cardiovascular symptoms, cardiovascular disorders were present in 27% (14/52). Among them, 15% (8/52) had myocardial injury, 8% (4/52) pulmonary embolisms, and 4% (2/52) both. The incidence of a severe condition (36% [5/14] vs. 8% [3/38], p = 0.014) and in-hospital cardiac events (71% [10/14] vs. 24% [9/38], p = 0.002) was significantly higher in patients with cardiovascular disorders than in those without. A multivariate logistic regression analysis revealed that a severe condition (OR, 5.789; 95% CI 1.442–45.220; p = 0.017) and in-hospital cardiac events (OR, 8.079; 95% CI 1.306–25.657; p = 0.021) were independent risk factors of cardiovascular disorders in cardiovascular long COVID patients.ConclusionsSuspicion of cardiovascular involvement in patients with cardiovascular long COVID in this study was approximately 30%. A severe condition during hospitalization and in-hospital cardiac events were risk factors of a cardiovascular sequalae in CV long COVID patients.